Clinical Aspects and Management of Levodopa-Induced Dyskinesia. (3rd June 2012) - Tambasco, Nicola; Simoni, Simone; Marsili, Erica; Sacchini, Elisa; Murasecco, Donatella; Cardaioli, Gabriela; Rossi, Aroldo; Calabresi, Paolo
Abstract : In Parkinson's disease, one of the most troublesome dilemmas is the treatment of levodopa-induced dyskinesia. After a few years, chronic treatment with levodopa is associated with the development of dyskinesias. Strategies to delay or to reduce dyskinesias are based on the change of levodopa dosing or the early use of dopamine agonists. Dopamine agonists with different pharmacological profile are available. Our paper was aimed to analyse the clinical impact and the management of dyskinesias with dopamine agonists.